Cosmogenic background rejection for the sterile neutrino search with the Short-Baseline Neutrino Program far detector - Hilgenberg, Christopher M., author; Wilson, Robert J., advisor; Harton, John, committee member; Toki, Walter, committee member; Zhu, Wen, committee member (Colorado State University. Libraries, 2020)
As the Short-Baseline Neutrino Program Far Detector, the ICARUS liquid argon time-projection chamber will operate at shallow depth and therefore be exposed to the full surface flux of cosmic rays. This poses a problematic background to the sterile neutrino search. A direct way to reject this background is to surround the cryostat with a detector capable of tagging incident cosmic muons with high efficiency, the Cosmic Ray Tagging System (CRT). I have worked to develop the CRT detector hardware and the simulation and reconstruction software. This system, currently undergoing installation, is approximately 25% commissioned and taking data. I have developed a powerful method for cosmogenic background rejection utilizing the CRT and Photon Detection System. Results from a simulation based study, informed by CRT data, demonstrate the power of the technique in rejecting cosmogenic events with little adverse impact on the neutrino sample.
Keywords: HEP experiment; neutrino oscillation; sterile neutrino; neutrino; cosmogenic background; scintillator tracker